Accelerating crystal structure determination with iterative AlphaFold prediction. Issue 3 (27th February 2023) - Terwilliger, Thomas C.; Afonine, Pavel V.; Liebschner, Dorothee; Croll, Tristan I.; McCoy, Airlie J.; Oeffner, Robert D.; Williams, Christopher J.; Poon, Billy K.; Richardson, Jane S.; Read, Randy J.; Adams, Paul D.
Abstract : AlphaFold predictions can be used both as a starting point for structure determination and as a method of model optimization. The Phenix PredictAndBuild tool automates iterative prediction and model building, yielding a density map and model starting with sequence information and crystallographic data. Abstract : Experimental structure determination can be accelerated with artificial intelligence (AI)‐based structure‐prediction methods such as AlphaFold . Here, an automatic procedure requiring only sequence information and crystallographic data is presented that uses AlphaFold predictions to produce an electron‐density map and a structural model. Iterating through cycles of structure prediction is a key element of this procedure: a predicted model rebuilt in one cycle is used as a template for prediction in the next cycle. This procedure was applied to X‐ray data for 215 structures released by the Protein Data Bank in a recent six‐month period. In 87% of cases our procedure yielded a model with at least 50% of C α atoms matching those in the deposited models within 2 Å. Predictions from the iterative template‐guided prediction procedure were more accurate than those obtained without templates. It is concluded that AlphaFold predictions obtained based on sequence information alone are usually accurate enough to solve the crystallographic phase problem with molecular replacement, and a general strategy for macromolecular structure determination that includes AI‐based prediction both as a starting point and as a method of model optimization is suggested.